Exploring the bottleneck of Iran's national innovation system by TOC thinking process - Abdi, Mansoureh; Hasanzadeh, Alireza; Fani, Ali-Asghar; Poor, Seyed Hassan Ghodsi (Technological and Economic Development of Economy, 2014)
This paper contributes to identify systematic problems in NIS using Thinking Process (TOC-TP) and to eliminate the bottlenecks, which results in improving the innovation process and efficiency of NIS. The Case study in this research is the NIS of Iran. The national documents of the innovation system were studied and all problems of NIS mentioned in documents were gathered. The causal relationships between the systematic problems were identified by the survey and grouped into 6 components by Exploratory Factor Analysis: weakness in technology diffusion mechanisms, the lack of centralized governance on science and technology policy, the government's pivotal role as an executor in education and research, weak laws and regulations in the field of research and technology, the lack of adequate financial resources in R&D and the lack of any perspective on the creation of wealth and entrepreneurship among the actors of research and technology. Finally the bottleneck of Iran's NIS was recognized by Thinking Process tools: the small participation of private sector in research and education system as the result of government's pivotal role as an executor of Iran's national innovation system. So the researchers could diagnose the policy gaps related to the identified bottlenecks.First published online: 11 Aug 2014